MARKETING ANALYSIS OF PUREBRED CHICKEN EGGS IN PADANG SIDEMPUAN CITY - Fauzan Towilan Daulay; Meriksa Sembiring; Risdawati Ginting (Journal of Innovation Research and Knowledge, 2024)
This research aims to find out about marketing channels, marketing margins and marketing efficiency of purebred chicken eggs in the city of Padang Sidempuan. This research was carried out in September 2023. The analysis examined is the marketing channel which consists of marketing channel I (Producer →Collector→ Retailer Consumer), marketing channel II (Producer→Retailer→Consumer), and marketing channel III (Producer→Collector→Consumer). The sampling technique in this research used a stratified random sampling technique. Stratified random sampling is a sampling method, where a heterogeneous population is divided into completely separate layers and from each layer (strata) can be taken randomly. This technique is used when the population has elemnts that are not homogeneous and are proportionally stratified so that each stratum can be represented in the sample. The data collected is primary data through interviews and questionnaires. The data analysis used in this research is descriptive analysis, marketing margin analysis and marketing efficiency of purebred chicken eggs in the city of Padang Sidempuan.The marketing Channels for purebred chicken eggs in Padang Sidempuan City have sufficient efficiency values with marketing channel III being the best channel of the three marketing with efficiency value of 2,76% and farmer’s share of 84,31%.